Glucocorticoids-based prodrug design: Current strategies and research progress - Hongbing Liu; Muse Ji; Peifu Xiao; Jingxin Gou; Tian Yin; Haibing He; Xing Tang; Yu Zhang (Asian Journal of Pharmaceutical Sciences, 2024)
Attributing to their broad pharmacological effects encompassing anti-inflammation, antitoxin, and immunosuppression, glucocorticoids (GCs) are extensively utilized in the clinic for the treatment of diverse diseases such as lupus erythematosus, nephritis, arthritis, ulcerative colitis, asthma, keratitis, macular edema, and leukemia. However, long-term use often causes undesirable side effects, including metabolic disorders-induced Cushing's syndrome (buffalo back, full moon face, hyperglycemia, etc.), osteoporosis, aggravated infection, psychosis, glaucoma, and cataract. These notorious side effects seriously compromise patients' quality of life, especially in patients with chronic diseases. Therefore, glucocorticoid-based advanced drug delivery systems for reducing adverse effects have received extensive attention. Among them, prodrugs have the advantages of low investment, low risk, and high success rate, making them a promising strategy. In this review, we propose the strategies for the design and summarize current research progress of glucocorticoid-based prodrugs in recent decades, including polymer-based prodrugs, dendrimer-based prodrugs, antibody-drug conjugates, peptide-drug conjugates, carbohydrate-based prodrugs, aliphatic acid-based prodrugs and so on. Besides, we also raise issues that need to be focused on during the development of glucocorticoid-based prodrugs. This review is expected to be helpful for the research and development of novel GCs and prodrugs.